A Case of Pericarditis Due to Roseomonas Gilardii in a Patient with Angiosarcoma of the Pericardium. (September 2013) - Santino, I.; Borghesi, R.; Alari, A.
Roseomonas gilardii is a Gram-negative slow growing coccobacillus that has been recognized as an opportunistic pathogen which can lead to infections, especially in immunocompromised and chronically ill patients. The organism is generally susceptible to carbapenems and aminoglycosides, but resistant to most of the cephalosporins. We report what we believe is the first case of a 72-year-old oncologic woman who developed a pericarditis caused by R. gilardii in Italy.